Effect of Single Post-Ovulatory Administration of Levonorgestrel on Gene Expression Profile During the Receptive Period of the Human Endometrium - Croxatto -Avoni, H; Velasquez, L (2012)
The hypothesis that levonorgestrel (LNG) used as an emergency contraceptive interferes with endometrial receptivity remains unproven.We compared the endometrial gene expression profile during the receptive period after administering a single dose of LNG 1.5 mg or placebo on day 1 of the luteal phase. An endometrial biopsy was done on day LH+7orLH+8 and samples were taken from seven volunteers, each one contributing with one cycle treated with placebo and another with LNG. The expression of 20 383 genes was determined using cDNA microarrays. Real-time RT-PCRwas used 1) to confirm the differences found in DNA microarray analysis and 2) to determine the effect of LNG on transcript levels of C3, C4BPa, COX2,MAOA, S100A4, andSERPINB9, known to be upregulated during receptivity, and on cPLA2?, JAK1, JNK1, CTSL1, andGSTP1, known to respond to mifepristone. Additional endometrial biopsieswere done during the pre-receptive (LH+3) and receptive (LH+7) period and samples were taken from eight untreated volunteers in order to determine the changes associated with acquisition of receptivity of 14 genes. Mean levels of PAEP, TGM2, CLU, IGF2, and IL6ST mRNAs increased after administering LNGwhile those ofHGD, SAT1, EVA1, LOC90133, ANXA1, SLC25A29, CYB5A,CRIP1, and SLC39A14 decreased.Except for the level ofANXA1transcript, all changesremained within the range observedin untreated controls, and none of the transcripts responding to mifepristone changed in response toLNG. Post-ovulatory administration of LNG caused minimal changes in gene expression profiling during the receptive period. Neither the magnitude nor the nature or direction of the changes endorses the hypothesis that LNG interferes with endometrial receptivity. © 2012 Society for Endocrinology.